Unintended Positive Consequences of Development Centres in University Graduates - White, Melissa; Becker, Jürgen; du Plessis, Marieta (Frontiers in Psychology, 2021)
This study investigated development centres as a method to improve the generalised self-efficacy of university graduates. This research was motivated by the various challenges graduates face in order to successfully transition into the world of work. Although there is a general scarcity of skills in many emerging economies like South Africa, graduate unemployment rates remain high. Additionally, graduates are not making the immediate impact that employers would expect due to a lack of technical and “soft skills”. General self-efficacy is an important attribute for job applicants because it provides them with the confidence to solve problems efficiently The primary research objective was to identify whether the generalised self-efficacy of graduates can be positively affected by a development centre approach in the short-term and long-term. The sample population for this research included Industrial Psychology graduates at a select university in the Western Cape, South Africa (n=17). A quasi-experimental methodology was implemented where an intervention group (n=7) and a control group (n=10) were taken through a development centre approach. The results of the intervention indicated that a development centre approach has a positive impact on self-efficacy levels over the short and medium term. Results from the study emphasise the importance of self-efficacy in graduate employability and indicate how development centres can be used to improve self-efficacy levels. The findings of this study provide a basis for future research into the further development of graduate self-efficacy and the potential benefits for first time job seekers.